2017
DOI: 10.1111/ocr.12153
|View full text |Cite
|
Sign up to set email alerts
|

Gene/environment interactions in craniosynostosis: A brief review

Abstract: It is suggested that craniosynostosis is caused by a heterogeneous set of effects including gene mutations, teratogenic exposure during critical periods of development, and gene/environment interactions. Distinguishing between sufficient, additive, and interactive effects is important to the study of gene/environment interactions and allows for segregation of environmental exposures effecting susceptible populations. Through the identification of sufficient and interactive effects efforts in prevention of cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…1). However, none of candidate germline or somatic mutations were proband-speci c. As geneenvironment interactions have been revealed in the pathogenesis of craniosynostosis [5,15], we wonder whether the adverse intrauterine exposures (environment) triggered the susceptible individual (II-1) to develop sagittal craniosynostosis. Based on this hypothesis, we re-analyzed our sequencing data and identi ed a heterozygous missense mutation of AXIN2 (c.1181G>A, p.R394H) in the leukocytes of subjects I-1, II-1 and II-2, and skull periosteum tissue of subject II-1.…”
Section: Mutation Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…1). However, none of candidate germline or somatic mutations were proband-speci c. As geneenvironment interactions have been revealed in the pathogenesis of craniosynostosis [5,15], we wonder whether the adverse intrauterine exposures (environment) triggered the susceptible individual (II-1) to develop sagittal craniosynostosis. Based on this hypothesis, we re-analyzed our sequencing data and identi ed a heterozygous missense mutation of AXIN2 (c.1181G>A, p.R394H) in the leukocytes of subjects I-1, II-1 and II-2, and skull periosteum tissue of subject II-1.…”
Section: Mutation Analysismentioning
confidence: 99%
“…The pathoetiology of NCS, involving interplay between genetic and environmental factors, is still not well de ned [5][6][7][8]. FGF ( broblast growth factor), BMP (bone morphogenic protein), Wnt (wingless-type integration sites) pathways are the major regulators in suture biology [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though treatments for birth defects have improved, they continue to be a major public health concern. This is due to the fact that the etiology of most birth defects remains unknown (Durham, Howie, & Cray, 2017;Harris et al, 2017;Khokha, Mitchell, & Wallingford, 2017). Thus, to develop strategies that either prevent or treat birth defects, we need to identify their underlying causes.…”
Section: Birth Defects Have Complex Etiologiesmentioning
confidence: 99%
“…Through genetic studies, tens of genes are shown to be associated with craniosynostosis (Twigg and Wilie, 2015), providing a foundation for further elucidation of the mechanism of the trait. Like any phenotypes, there should also be environmental contributions to craniosynostosis (Shashi and Hart, 2002; Zeiger et al, 2002; Durham et al, 2017), illustrated by an observation of identical twins with discordant craniosynostosis (Magge et al, 2017).…”
Section: Introductionmentioning
confidence: 99%